Synthesis and characterization of polyaniline for hydrazine detection / Kavirajaa Pandian Sambasevam - Kavirajaa Pandian, Sambasevam (2015)
Among the conducting polymers, polyaniline (PAni) is studied most extensively due to the ease of synthesis, high conductivity and low production cost. Hydrazine from fuels, pesticide and corrosion inhibitor industries are a toxic compound which can cause neurotoxicity and carcinogenicity. In this study, a series of PAni were synthesized and applied as a chemical sensor for hydrazine detection. The sensor responses of PAni were monitored by ultraviolet-visible (UV-Vis) analysis in hydrazine detection. Besides, the sensor response was supported by conductivity study and Fourier transform infrared (FTIR) analysis to identify the chemical interaction between the PAni and the hydrazine. Doped-PAni were synthesized through chemical oxidative polymerization by using different sodium dioctyl sulfosuccinate salt dopant ratio (monomer:dopant = 5:3,5:5,5:7) under various polymerization temperatures (-10 ˚C to 25 ˚C). Similar procedure was repeated by addition of TiO2 nanoparticles (10 – 40%) through in-situ polymerization to produce PAni/TiO2 nanocomposites. FTIR, UV-Vis and x-ray diffractometry (XRD) analysis confirmed the chemical structure of all PAni. Conductivity, morphology and elemental analysis of doped-PAni were studied by resistivity meter, field emission scanning electron microscope (FESEM) and energy dispersive x-ray (EDX) analysis, respectively. For chemical sensor study, all PAni showed significant decrease at polaron peak (~780 nm) in UV-Vis spectra upon immersion in hydrazine. Doped-PAni synthesized with highest dopant ratio (5:7) at subzero polymerization temperature (-5 ˚C) provided more reactive sites to interact with hydrazine, thus giving rapid response time (7 s) with highest sensitivity compare to those with lower dopant ratio and other temperatures. Besides, PAni/TiO2 nanocomposites (5:7, -5 ˚C) with addition of 20% TiO2 offered good synergetic effect between PAni and TiO2 in order to detect hydrazine more effectively. The conductivity response for PAni (5:7, -5 ˚C, 20% TiO2) in hydrazine detection showed significant decrease in conductivity due to the reduction by hydrazine to convert conducting PAni (emeraldine salt-ES) to insulating PAni (leucoemeraldine-LE). Besides that, FTIR analysis of PAni showed decrease in the intensity ratio of quinoid/benzenoid (IQ/IB) from ~1 to 0.80 (increment in benzenoid units) upon immersion of PAni in hydrazine. FTIR analysis showed good agreement with conductivity data because LE consists of more benzenoid unit compared to ES. PAni (5:7, -5 ˚C, 20% TiO2) exhibited good reusability up to 10 cycles and excellent selectivity in the presence of interfering species such as 2-propanol, sodium hydroxide, formic acid and ammonia in hydrazine detection. The method validation of PAni (5:7, -5 ˚C, 20% TiO2) by UV-Vis measurement showed a linear calibration curve for hydrazine (0.05 – 5.00 ppm) with good correlation coefficient of 0.9928 and limit of detection (LOD) of 0.05 ppm (lower than OSHA standard:1 ppm). PAni (5:7, -5 ˚C, 20% TiO2) showed excellent recovery (93 – 105 %) and good relative standard deviation (R.S.D.) (0.3 – 4.2 %) for spiked real samples in laboratory tap water and river water (0.5 – 1.0 ppm) during hydrazine detection. In conclusion, PAni (5:7, -5 ˚C, 20% TiO2) that exhibited rapid response, highest sensitivity, satisfactory recovery (real sample), good reusability and selectivity is highly recommended as chemical sensor for hydrazine detection.